2016
DOI: 10.1187/cbe.16-02-0089
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Collaborative Series of Classroom-Based Undergraduate Research Experiences Spanning Chemical Biology, Biochemistry, and Neurobiology

Abstract: This paper describes the design, implementation, and assessment of three collaborative classroom undergraduate research experiences (CUREs) integrating faculty research interests across chemical biology, biochemistry, and neurobiology. Benefits of CURE participation included increased faculty productivity, generation of novel scientific data, and the expected CURE benefits for student learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 56 publications
(163 reference statements)
1
29
0
Order By: Relevance
“…The enzymatic activity of ybfF, Rv0045c, and their variants was measured against the fluorogenic SAR library (Fig. 1) using a 96-well microplate assay (31,35,77). Fluorogenic substrates were prepared as stock solutions in DMSO (10 mM) and were diluted into PBS containing acetylated BSA (PBS-BSA; 0.1 mg/ml) to a starting concentration of 100 M. Acetylated BSA was added to reduce nonspecific adsorption to the plasticware common in microplate analysis (29).…”
Section: Kinetic Measurements With Fluorogenic Sar Librarymentioning
confidence: 99%
“…The enzymatic activity of ybfF, Rv0045c, and their variants was measured against the fluorogenic SAR library (Fig. 1) using a 96-well microplate assay (31,35,77). Fluorogenic substrates were prepared as stock solutions in DMSO (10 mM) and were diluted into PBS containing acetylated BSA (PBS-BSA; 0.1 mg/ml) to a starting concentration of 100 M. Acetylated BSA was added to reduce nonspecific adsorption to the plasticware common in microplate analysis (29).…”
Section: Kinetic Measurements With Fluorogenic Sar Librarymentioning
confidence: 99%
“…Many of the items on the survey focused on learning specific subject matter, and we did not expect students to have learned many facts, but rather we expected that gains would be apparent in specifically those items addressing working in groups, on working on problems without clear solutions, on data collection/organization and interpretation, and on using this technology and related data to describe the complexity of human movement. The capacity of the RISC survey or its components to measure students increasing dexterity with these research skills has been demonstrated repeatedly in inquiry-driven science classrooms (Burnette & Wessler, 2013;Call et al, 2007;Clark et al, 2009;Jordan et al, 2014;Kowalski, Hoops & Johnson, 2016;Lopatto et al, 2008;Mader et al, 2017;Makarevitch, Frechette & Wiatros, 2015;Miller et al, 2013;Reed & Richardson, 2013;Staub et al, 2016;Sarmah et al, 2016). We hoped to identify whether there were post-course gains that might exceed the average of all students responding to the RISC that semester.…”
Section: The Risc Surveymentioning
confidence: 98%
“…Many of the items on the survey focused on learning specific subject matter, and we did not expect students to have learnt many facts; rather we expected that gains would be apparent in specifically those items addressing working in groups, working on problems without clear solutions, on data collection/organisation and interpretation, and on using this technology and related data to describe the complexity of human movement. The capacity of the RISC survey or its components to measure students' increasing dexterity with these research skills has been demonstrated repeatedly in inquiry-driven science classrooms (Burnette and Wessler 2013;Call et al 2007;Clark et al 2009;Jordan et al 2014;Kowalski, Hoops and Johnson 2016;Lopatto et al 2008;Mader et al 2017;Makarevitch, Frechette and Wiatros 2015;Miller et al 2013;Reed and Richardson 2013;Sarmah et al 2016;Staub et al 2016). We aimed to identify whether there were post-course gains that might exceed the average of all students responding to the RISC of that semester.…”
Section: The Risc Surveymentioning
confidence: 99%